2009
DOI: 10.1111/j.1471-0528.2008.02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Ear acupuncture or local anaesthetics as pain relief during postpartum surgical repair: a randomised controlled trial

Abstract: Objective To evaluate two methods of pain relief during postpartum surgical repair in regard to effectiveness, wound healing and patient evaluation.Design A randomised controlled trial testing a pragmatic set-up of brief training of clinicians.Setting Delivery ward at a Danish district hospital with approximately 1600 annual deliveries.Population Primiparous women with a vaginal delivery at term who needed surgical repair of lacerations to the labia or the vagina, perineal lacerations of first or second degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
0
16
0
7
Order By: Relevance
“…Another RCT (13) with 207 women compared the use of auriculotherapy with usual treatment (local anaesthetic) for episiotomy repair and perineal lacerations on pain control. In this study, pain during the surgical procedure was more frequent among women allocated into the auriculotherapy group (89% versus 54%, p <0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Another RCT (13) with 207 women compared the use of auriculotherapy with usual treatment (local anaesthetic) for episiotomy repair and perineal lacerations on pain control. In this study, pain during the surgical procedure was more frequent among women allocated into the auriculotherapy group (89% versus 54%, p <0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In Berlit and colleagues' investigation, the addition of prilocaine (31% in the study and 2% in the control groups) was necessary and the satisfaction did not significantly differ between 2 groups (19). Gutton et al (23) reported an improvement in analgesia and maternal satisfaction when ropivacaine was used in contrast to lidocaine for perineal infiltration post-episiotomy, and in the study of Kindberg et al (18) satisfaction from acupuncture was significantly lower than that from lidocaine (P = 0.01).…”
Section: Discussionmentioning
confidence: 95%
“…The statistically significant findings of this study indicated that N 2 O may be effective in alleviating pain intensity during episiotomy repair when compared with lidocaine (P = 0.005). The study of Kindberg et al (18) showed that lidocaine was more effective compared with acupuncture in reducing the pain intensity during the episiotomy repair. In a clinical trial published by Berlit et al (19), the statistical difference between N 2 O and lidocaine in reducing the pain during the repair of genital lacerations was not significant (P = 0.69), which was not consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In an investigation done by Berlit et al, the addition of prilocaine (31% in study group and 2% in control group) was necessary and the satisfaction does not significantly differ between the 2 groups (19). Gutton et al (23) reported an improvement in analgesia and maternal satisfaction when ropivacaine versus lidocaine was used for perineal infiltration postepisiotomy and in the study of Kindberg et al (18) satisfaction with acupuncture was significantly lower than lidocaine (P value = 0.01). The most prevalent side effect in this study was dizziness.…”
Section: Discussionmentioning
confidence: 97%
“…The statistical significant findings of this study indicate that N 2 O may be effective in reducing pain intensity during episiotomy repair when compared with Lidocaine (P value = 0.005). The study of Kindberg et al (18) showed that lidocaine was more effective in reducing pain intensity during episiotomy repair compared with acupuncture. In a clinical trial published by Berlit et al (19), the difference between N 2 O and lidocaine in reducing pain during the repair of genital lacerations was not statistically significant (P value = 0.69), which was not consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%